BEYOND THE ABUSE OF POWER AND THE ABUSE OF CONSCIENCE: Charting a Course for Theological Ethics in Response to the Sexual Abuse Crisis in the Australian Catholic Church - Fleming, Daniel J. (Asian Horizons, 2020)
This article has a modest, but important, goal. It seeks to chart a course in a hitherto underdeveloped area of theological ethics: responding to the crisis of sexual abuse in the Church. Drawing on the Catholic theology of conscience in dialogue with the philosophy of Emmanuel Levinas, it argues that the crisis can be understood as a failure of conscience to attend to the ethical call, resulting from a form of moral blindness created by implicit belief systems within the Church. A response is suggested which is framed around Christina A. Astorga’s threefold process of lament, resistance and kinship.